دمج تقنيات الذكاء الاصطناعي في المحاسبة وأثره على مستقبل مهنة المحاسبة في الجزائر - بن تركية ،نجاة (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة إلى التعرف على الاطار النظري للذكاء الاصطناعي واستخدامه في الجانب المحاسبي، وأثر ادخال تقنيات الذكاء الاصطناعي على مهنة المحاسبة في الجزائر من خلال دراسة آراء عينة من المهنيين والمحاسبين، وقد خلصت الدراسة إلى أن اعتماد تقنيات الذكاء الاصطناعي في المجال المحاسبي له دور كبير في تحسين اجراءات العمل المحاسبي وخفض التكاليف، ومع ذلك فإنه يمثل تحدي كبير للمحاسبين والمهنيين من عدة جوانب أبرزها التحديات المالية والأمنية المتعلقة باستخدام الذكاء الاصطناعي، اضافة إلى التحديات التي يفرضها على المهنيين والمحاسبين لمواكبة التطورات الحاصلة في هذا المجال والاستغناء عن الطرق التقليدية في العمل، كما توصلت الدراسة إلى أن الذكاء الاصطناعي سيؤدي إلى تغير الأدوار التقليدية للمحاسبين غير أنه لا يمكن أن يكون بديلا عنهم بشكل كامل. This study aims to examine the theoretical framework of artificial intelligence (AI) and its application in the accounting field, while analyzing the impact of AI technologies on the accounting profession in Algeria through a survey of professionals and accountants. The study concludes that the adoption of AI in accounting significantly enhances procedural efficiency and reduces costs. However, it poses substantial challenges for accountants and professionals, particularly in terms of financial and security concerns associated with AI use, in addition to the pressure on professionals to keep up with technological advancements and shift away from traditional practices.Furthermore, the study finds that AI will transform the traditional roles of accountants, though it cannot fully replace them.
The Integration of AI in Accounting and Their Impact on the Future of the Accounting profession in Algeria – An Exploratory Study
Keywords: الذكاء الاصطناعي; مهنة المحاسبة; الجزائر; Artificial Intelligence; Accounting Profession; Algeria